Einstein : his life and universe - Isaacson, Walter (New York : Simon & Schuster, 2007)
The first full biography of Albert Einstein since all of his papers have become available shows how his scientific imagination sprang from the rebellious nature of his personality. Biographer Isaacson explores how an imaginative, impertinent patent clerk--a struggling father in a difficult marriage who couldn't get a teaching job or a doctorate--became the locksmith of the mysteries of the atom and the universe. His success came from questioning conventional wisdom and marveling at mysteries that struck others as mundane. This led him to embrace a morality and politics based on respect for free minds, free spirits, and free individuals. These traits are just as vital for this new century of globalization, in which our success will depend on our creativity, as they were for the beginning of the last century, when Einstein helped usher in the modern age.--From publisher description
The light-beam rider -- Childhood, 1879-1896 -- The Zurich Polytechnic, 1896-1900 -- The lovers, 1900-1904 -- The miracle year: quanta and molecules, 1905 -- Special relativity, 1905 -- The happiest thought, 1906-1909 -- The wandering professor, 1909-1914 -- General relativity, 1911-1915 -- Divorce, 1916-1919 -- Einstein's universe, 1916-1919 -- Fame, 1919 -- The wandering Zionist, 1920-1921 -- Nobel laureate, 1921-1927 -- Unified field theories, 1923-1931 -- Turning fifty, 1929-1931 -- Einstein's God -- The refugee, 1932-1933 -- America, 1933-1939 -- Quantum entanglement, 1935 -- The bomb, 1939-1945 -- One-worlder, 1945-1948 -- Landmark, 1948-1953 -- Red scare, 1951-1954 -- The end, 1955 -- Epilogue: Einstein's brain and Einstein's mind
Includes bibliographical references (p. 553-564) and index
Keywords: Einstein, Albert, -- 1879-1955; Einstein, Albert, -- 1879-1955 -- Friends and associates; Physicists -- Biography; Relativity (Physics); Unified field theories